Determinants of diabetes mellitus among adults aged ≥40 years: A case-control study in Banda Aceh - Asri Jumadewi; Darmawati Darmawati; Erlinawati Erlinawati; Astrid Siska Pratiwi (AcTion: Aceh Nutrition Journal, 2026)
Diabetes mellitus is characterized by hyperglycemia and remains a growing global public health concern, including in Aceh Province, Indonesia. Several determinants have been associated with its occurrence, including age, obesity, physical inactivity, smoking, and family history. This study aimed to investigate the association between obesity, physical activity, smoking habits, family history, and diabetes mellitus. A case–control study was conducted among 46 participants, consisting of 23 patients with diabetes mellitus and 23 non-diabetic controls who underwent laboratory examinations at the Clinical Pathology Laboratory of Dr. Zainoel Abidin Regional General Hospital in Banda Aceh. Primary data were collected through interviews and structured questionnaires, and secondary data were obtained from medical records between January and August 2023. Data were analyzed using univariate analysis, chi-square tests, and multivariate logistic regression. The prevalence of diabetes mellitus was 5.9% in women and 5.2% in men. Obesity was significantly associated with diabetes mellitus (p < 0.001), with an odds ratio of 23.02. In contrast, physical activity, smoking status, and family history of diabetes showed no significant association with diabetes mellitus (p > 0.05). In conclusion, obesity is a major risk factor for diabetes mellitus. Regular monitoring and control of the body mass index are essential strategies for maintaining an ideal body weight and reducing the risk of diabetes mellitus.